Temperature-Dependent Conformational Changes in Herpes Simplex Virus ICP4 That Affect Transcription Activation - Compel, Peter (American Society for Microbiology, 2003)
The C-terminal 500 amino acids of herpes simplex virus type 1 ICP4 are required for full activator function and viral growth and are known to participate in interactions consistent with the role of ICP4 as an activator of transcription. Oligonucleotide mutagenesis was used to target stretches of amino acids that are conserved with the ICP4 analogs of other alphaherpesviruses and were also predicted to be exposed on the surface of the molecule. Seven mutants were isolated that possessed one to three amino acid changes to the residue alanine in four regions between residues 1000 and 1200. The mutants generated were analyzed first in transfection assays and subsequently after introduction into the viral genome. A number of phenotypes representing different degrees of functional impairment were observed. In transient assays conducted at 37°C, mutant M2 was indistinguishable from wild-type ICP4. Mutants M6 and M7 were marginally impaired. M3, M4, and M5 were more significantly impaired but still able to activate transcription, and M1 was completely impaired. In the context of the viral genome, M1, M3, and M7 were found to be temperature sensitive for growth. All three overproduced immediate-early (IE) proteins at the nonpermissive temperature (NPT). M3 and M7 produced early but not late proteins, and M1 produced neither early nor late proteins, at the NPT. The ICP4 proteins synthesized by all of the mutants tested were able to bind to specific ICP4 binding sites in electrophoretic mobility shift experiments. However, the DNA-protein complexes formed with the ICP4 from M1, M3, or M7 produced at the NPT possessed altered mobility. These complexes were not supershifted by a monoclonal antibody that recognizes an epitope in the C terminus; however, they were supershifted by a monoclonal antibody that recognizes the N terminus. The results suggest that the mutant forms of ICP4, while able to bind to DNA, are conformationally altered at the NPT, thus impairing the ability of the protein to activate transcription to different extents. The complete lack of ICP4 function characteristic of the M1 protein, and the inability of all the mutants to attenuate IE gene expression, suggest that the mutations additionally affect functions of the N terminus to different extents.